Hubungan Dukungan Sosial dengan Kualitas Hidup Pada Pasien Fraktur Ekstremitas Bawah di RSUD Meuraxa Banda Aceh - Abdurrahman Abdurrahman; Cut Mutiah; M. Fardi Aulia (Malahayati Nursing Journal, 2022)
ABSTRACT : RELATIONSHIP OF SOCIAL SUPPORT WITH QUALITY OF LIFE IN LOWER EXTREMITY FRACTURE PATIENTS AT RSUD MEURAXA BANDA ACEH  Introduction : The incidence of fractures in the world is increasing, according to WHO, in 2012 there were as many as 13 million people (2.7%) experiencing fractures, in 2013 it increased to 18 million people (4.2%) in 2014 there was another increase of 21 million people (7.5%). In Indonesia, fracture is the third leading cause of death after heart disease and tuberculosis. Patients with fractures cannot carry out their own activities so that sufferers experience stress, so that it can affect psychologically and will have an impact on the patient's quality of life.Purpose: To determine the relationship between social support and quality of life in patients with lower extremity fractures.Method: The research design used was analytic with a cross sectional approach. This research was carried out in the Ar Rayyan Inpatient Room, Meuraxa Hospital, Banda Aceh. Sampling using purposive sampling technique with a total sample of 57 people. The instrument used is in the form of a questionnaire. hypothesis testing using Chi-Square statistical test.Result: The results showed that there was a relationship between emotional support for extremity fracture patients (P= 0.012), there was a relationship between instrumental support for extremity fracture patients (P- 0.034), there was a relationship between informational support for extremity fracture patients (P=005) and there was a relationship between assessment support in patients with esternal fractures (P = 0.028).Conclusion: there is a relationship between emotional support, instrumental support, informational support and assessment support with quality of life in patients with osseous fractures. Keywords: Social Support, Quality of Life, Lower Extremity Fracture       INTISARI: HUBUNGAN DUKUNGAN SOSIAL DENGAN KUALITAS HIDUP PADA PASIEN FRAKTUR EKSTREMITAS BAWAH DI RSUD MEURAXA BANDA ACEH Latar Belakang: Angka kejadian fraktur didunia semaking bertambah, menurut WHO tercatat pada tahun 2012 ada sebanyak 13 juta jiwa (2,7%) mengalami fraktur, pada tahun 2013 meningkat menjadi 18 juta jiwa ( 4,2%) pada tahun 2014 terjadi peningkatan lagi sebanyak 21 juta jiwa (7,5%). Di Indonesia fraktur merupakan penyebab kematian ketiga terbesar dibawah penyakit jantung dan tuberculosis. Penderita dengan fraktur tidak dapat melakukan kegiatan sendiri sehingga para penderita mengalami stress, sehingga dapat mempengaruhi psikologis dan akan berdampak pada kualitas hidup penderita.Tujuan : Untuk mengetahui ada hubungan dukungan sosial dengan kualitas hidup pada pasien fraktur ekstremitas bawah Di RSUD Meuraxa Banda AcehMetode Penelitian : Desain penelitian yang digunakan adalah analitik dengan pendekatan cross sectional. penelitian ini dilaksanakan di Ruang Rawat Inap Ar Rayyan RSUD Meuraxa Banda Aceh. Pengambilan sampel sengan menggunakan teknik purposive sampling dengan jumlah sampel sebanyak 57 orang. intrumen yang digunakan yaitu berupa angket. uji hipotesis menggunakan uji statistik Chi-Square.Hasil : Hasil penelitian didapatkan bahwa terdapat hubungan antara dukungan emosional  pada pasien fraktur ekstermitas (P= 0,012), ada hubungan antara dukungan instrumental pada pasien fraktur ekstermitas (P- 0,034), ada hubunga dukungan informasi pada pasien fraktur ekstermitas (P=005) dan ada hubungan antara dukungan penilaian pada pasien fraktur estermitas (P= 0,028).Kesimpulan : terdapat hubungan antara dukungan emosional, dukungan instrumental, dukungan informasi dan dukungan penilaian dengan kualitas hidup pada pasien fraktur estermitas. Kata Kunci: Dukungan Sosial, Kualitas Hidup, fraktur ekstermitas bawah